Systematic metabolic engineering of Zymomonas mobilis for β-farnesene production - Xiao, Yubei; Tan, Xuemei; He, Qiaoning; Yang, Shihui (Frontiers in Bioengineering and Biotechnology, 2024)
1. Five β-farnesene synthases screened with AaBFS selected for β-farnesene production in Zymomonas mobilis.2. β-farnesene production improved by increasing the expression of AaBFS using strong promoter or multiple copies through multiple-plasmid constructs or genomic multi-locus integration.3. MEP flux enhancement crucial for increasing β-farnesene production by enhancing the expression of key enzymes of DXS, IspG, and IspH. 4. β-farnesene production improved by optimizing aeration and C/N ratios.5. The highest β-farnesene titer of 159.7 mg/L achieved for recombinant Z. mobilis in flask fermentation.